Um estudo longitudinal das representações dos afrodescendentes em propagandas impressas 1980-2010 - Faria, Sibele Gomes de Santana (2011)
The aim of this thesis is to identify the evolution of representations of African descent in print advertisements in newspapers of wide circulation in Brazil, covering the period 1980 to 2010. Within the evolution of such representation of African descent in Brazil, the question to investigate is to find out if there is a pattern that can be identified in terms of their roles in the print media. If properly demonstrated, this finding may have a significant detrimental impact in both the construction of the identity of Brazilians of African descent and the perception of society in relation to this racial group, promoting the persistence of discriminatory practices. Following the approach on the evolution of social representations of minorities in the media Clark (1969), it is possible to construct the proposition that the advertisements follow a particular timeline to representations of African descent in the print media, divided into four phases: non-recognition, ridicule, regulation and respect. The dissertation seeks to support this proposition in three complementary theoretical frameworks: (i) the concept of ideology developed by Thompson (2007, 2009); (ii) stigma as a mode of operation of ideology - theory originally built by Goffman (1963); and (iii) the setting 'established-outsiders' developed by Elias and Scotson (1965), which seeks to explain the dynamics of discrimination. The methodological approach is based on content analysis as it is used by Kassarjian (1977) consecrated in the area of consumer behavior, which is characterized according to the author as a quantitative approach. The Research Unit is print ads of the two largest circulation newspapers in Brazil: a Folha de São Paulo and Estado de São Paulo. This methodology is quite well utilized in the area of consumer behavior and can be characterized as a quantitative method. The research unit is constituted by print advertisements taken from two major newspapers in Brazil: Folha de Sao Paulo and the Estado de São Paulo. The findings point to a partial acceptance of the Clark chronology, showing some progress in the representation of African descent in print advertising.